GEOTECHNICAL INVESTIGATION OF BLACK COTTON SOIL AROUND DEBA AREA, NORTH-EASTERN NIGERIA - K. G, ADAMU; A, SULAIMAN; E. Y, MBIIMBE; M, RABI’U (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
This geological and geotechnical study was carried out to investigate the engineering properties of black cotton soil around Gombe – Deba area and environs. Geological field survey was carried out around the study area and geotechnical laboratory analysis comprising of Atterbergs limits, linear shrinkage, natural moisture content, CBR, UCS, and compaction test was conducted on four different soil samples collected from the field. The study area is underlain by the Pindiga and Gombe formations and the main lithological units are limestone, shale, sandstone with large superficial deposits of Black cotton soil covering the study area. The results of the geotechnical analysis revealed low unconfined compressive strength value of 116.6KN/m2 as the maximum of the four samples analyzed, CBR values for the soaked test are 3%, 4.6%, 4.5% and 4.3% and the unsoaked values of 9.1%, 8.5%, 8.8% and 7.5% for pits no. 1,2, 3, and 4 respectively. The OMC values of 24.03% and 19% with corresponding MDD of1.33mg/m3 and 1.53mg/m3 were obtained as the maximum and minimum values respectively. The soil of the study area show a high liquid limit with an average value of 62% and high plasticity index having average of 35%. These results indicates that the black cotton soil of the area fall within the CH group and A-7-6 group and are considered as weak materials in engineering construction. In addition these soils are highly expansive; hence need to be suitably stabilized to upgrade the engineering performance of the soils.